Water quality and daily temperature cycle affect biofilm formation in drip irrigation devices revealed by optical coherence tomography. Issue 3 (16th March 2017) - Qian, Jueying; Horn, Harald; Tarchitzky, Jorge; Chen, Yona; Katz, Sagi; Wagner, Michael
Abstract: Drip irrigation is a water-saving technology. To date, little is known about how biofilm forms in drippers of irrigation systems. In this study, the internal dripper geometry was recreated in 3-D printed microfluidic devices (MFDs). To mimic the temperature conditions in (semi-) arid areas, experiments were conducted in a temperature controlled box between 20 and 50°C. MFDs were either fed with two different treated wastewater (TWW) or synthetic wastewater. Biofilm formation was monitored non-invasively and in situ by optical coherence tomography (OCT). 3-D OCT datasets reveal the major fouling position and illustrate that biofilm development was influenced by fluid dynamics. Biofilm volumetric coverage of the labyrinth up to 60% did not reduce the discharge rate, whereas a further increase to 80% reduced the discharge rate by 50%. Moreover, the biofilm formation rate was significantly inhibited in daily temperature cycle independent of the cultivation medium used.